Primary School Teachers' Knowledge of the Pedagogical Content of "Ratio and Proportion" in Sixth and Seventh Grades: A case Study - Sally Shatara; Refa' Ramahi (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This qualitative case study aimed to investigate the primary school teachers' pedagogical content knowledge of Ratio and Proportion for Sixth and seventh grades based on the theoretical framework, the model of PCK developed by  (Hashweh, 2005). Sixth and seventh grades mathematics teachers, who work in private schools in Ramallah & Al_Bireh cities, were chosen to answer the questionnaire related to the pedagogical content knowledge. After that, the teacher with the highest grades was chosen and considered as a case study. In addition to the questionnaire, both the interviews and observations were used in order to answer the research question. The results showed that the content knowledge, the goals knowledge and the resource knowledge did not exceed the text book's content. Despite the fact that she showed a good knowledge of the characteristics of the students in terms of individual differences, she was unable to discover the misconceptions. However, her teaching style and evaluation strategies were most often traditional, with limited assignments and homework. Her horizontal knowledge was better due to teaching more than one secondary grade level, while her vertical knowledge did not exceed the book examples.   Finally, she ignored preparation for her class and depended heavily on her teaching experience which negatively affected class management. The study recommends that teachers have to reflect on what they do to better deal with students and deliver the needed material in a way that reflects the new teaching methods. In addition, the study suggests attending training workshops for improvement and development.